GLP-1 and GLP-1/GIP Incretin Agonists and Related Therapies in Metabolic Obesity: A Narrative Review of Pivotal Trials, Pathophysiological Foundations, and Practical Management of Complications - Belmontes - Gutiérrez , D.A.,; Jaramillo - Santos , J.,; Isais – Moreno , D.M;; Hernández - Aguirre , U.G.,; Pérez – Silva , I.A (Revista de Ciencias Médicas Torreón, 2026)
The rapid adoption of glucagon-like peptide-1 receptoragonists,GLP-1/glucose-dependentinsulinotropicpolypeptide coagonists and related incretin-based therapieshas reshaped the management of obesity, type 2 diabetes andcardiometabolic complications. Nevertheless, widespreaduse outside appropriate medical settings has raised concernsabout prescribing by untrained personnel, non-regulatedmagnitud absoluta del efecto, eventos adversosyproducts,inadequatetitrationandinsufficientgastrointestinal, renal, nutritional and glycemic follow-up.This narrative review summarizes the pivotal trials and majorreal-world evidence supporting current prescriptions ofliraglutide, dulaglutide, semaglutide, tirzepatide andemerging therapies. A standardized clinical framework isused across studies: population, intervention, comparator,primary endpoint, absolute effect size, safety andapplicability. The review also expands the mechanisticrationale by which weight loss and potentially weight-independent pharmacologic actions may influencecardiovascular disease, heart failure with preserved ejectionfraction, chronic kidney disease, obstructive sleep apnea,osteoarthritis, polycystic ovary syndrome and metabolicdysfunction-associated steatotic liver disease. Practicalrecommendations are provided for hypoglycemia prevention,dehydration, acute kidney injury, lean mass preservation andgastrointestinal adverse event management, includinginsulin/sulfonylureaadjustment,hydration,proteinprescription and resistance training.
Keywords: Nursing workload, Critical care, Intensive Care Unite.